Conduit position and connectivity affect the likelihood of xylem embolism during natural drought in evergreen woodland species. (14th April 2022) - Pritzkow, Carola; Brown, Matilda J M; Carins-Murphy, Madeline R; Bourbia, Ibrahim; Mitchell, Patrick J; Brodersen, Craig; Choat, Brendan; Brodribb, Timothy J
Abstract: Background and Aims: Hydraulic failure is considered a main cause of drought-induced forest mortality. Yet, we have a limited understanding of how the varying intensities and long time scales of natural droughts induce and propagate embolism within the xylem. Methods: X-ray computed tomography (microCT) images were obtained from different aged branch xylem to study the number, size and spatial distribution of in situ embolized conduits among three dominant tree species growing in a woodland community. Key Results: Among the three studied tree species, those with a higher xylem vulnerability to embolism (higher water potential at 50 % loss of hydraulic conductance; P 50 ) were more embolized than species with lower P 50 . Within individual stems, the probability of embolism was independent of conduit diameter but associated with conduit position. Rather than the occurrence of random or radial embolism, we observed circumferential clustering of high and low embolism density, suggesting that embolism spreads preferentially among conduits of the same age. Older xylem also appeared more likely to accumulate embolisms than young xylem, but there was no pattern suggesting that branch tips were more vulnerable to cavitation than basal regions. Conclusions: The spatial analysis of embolism occurrence in field-grown trees suggests that embolism under natural drought probably propagates by air spreading from embolized into neighbouring conduits in a circumferential pattern. This pattern offers the possibility to understand the temporal aspects of embolism occurrence by examining stem cross-sections.